KOMPETENSI GURU BAHASA ARAB DALAM MENGIMPLEMENTASIKAN KURIKULUM 2013 - Titin Fatimah (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2020)
The 2013 curriculum in Arabic subjects is same as the demands of learning procedures for other subjects that require teacher responsibility and competence in implementing creatively and innovatively. The ideality of learning in the 2013 Curriculum in fact has not been realized as it should be because it is related to aspects of teacher competence. Pedagogic competence, as one of the aspects of competence that is absolutely inherent in teachers, is still found in the field to be insufficient for teachers, including Arabic teachers at MTs. Negeri Palu, especially in the sub-competency ability to design and develop learning plans according to the 2013 Curriculum standards and the demands of strengthening literacy, Higher of Thingking Skills (HoTS) and 4C. The Problem to the implementation and application of teacher pedagogical competences are grouped into two categories, namely: internal constraints and external constraints so that serious and strategic efforts are needed to overcome the weaknesses of teacher competence in learning